Healthcare Costs Among Adults with Type 2 Diabetes Initiating DPP-4 Inhibitors. Issue 1 (January 2016) - Farr, Amanda; Sheehan, John; Brouillette, Matthew; Smith, David; Johnston, Stephen; Kalsekar, Iftekhar
Abstract Introduction Oral antidiabetes medications, including dipeptidyl peptidase-4 inhibitors (DPP-4is) saxagliptin and sitagliptin, are used for the treatment of type 2 diabetes (T2D). The study objective was to compare all-cause and diabetes-related costs following initiation of saxagliptin or sitagliptin. Methods Patients aged ≥18 years initiating saxagliptin or sitagliptin between January 1, 2009 and January 31, 2012 in the Truven Health MarketScan Commercial and Medicare Supplemental databases were identified. Patients were required to have continuous enrollment for ≥365 days before and ≥365 days after the index date (date of the first saxagliptin or sitagliptin claim). Additionally, patients were required to have a claim with a T2D diagnosis (ICD-9-CM 250.×0, 250.×2) and no claims for a DPP-4i medication before the index date. All-cause and diabetes-related medical costs and total costs (including pharmacy costs) were captured over the 1-year follow-up period. Generalized linear models with log link and gamma distribution were fit to compare costs between the two cohorts using cost ratios, controlling for patient baseline characteristics. Recycled prediction methods were used to generate adjusted predicted costs and confidence intervals. Results The final sample comprised 3354 saxagliptin initiators and 26, 895 sitagliptin initiators. The average age of saxagliptin and sitagliptin initiators was 57 years and just over 50% were males. After adjusting for baseline characteristics, saxagliptin patients had significantly lower average all-cause medical costs (cost ratio = 0.901, P < 0.001; predicted mean costs: 8687 vs. 9646) compared with sitagliptin patients over the 1-year follow-up. Findings were consistent for diabetes-related medical costs (cost ratio = 0.890, P < 0.001; predicted mean costs: 2180 vs. 2450). Total costs were also lower for saxagliptin initiators (cost ratio = 0.950, P = 0.002; predicted mean costs: 13, 911 vs. 14, 651) over the 1-year follow-up period. Conclusion Initiation of treatment with saxagliptin was associated with lower medical costs over 1 year compared with initiation of sitagliptin among adults with T2D. Funding AstraZeneca.